The Role of Community and Local Wisdom in Minimizing Islamic Fanaticism and Maintaining Islamic Culture in Masin Village - Ahmad Badawi; Bagas Heradhyaksa (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
Religious fanaticism is one of the challenges in maintaining religious harmony in Indonesia. Masin Village, Batang Regency, Central Java, has local wisdom that can play a role in minimizing Islamic religious fanaticism and maintaining Islamic culture. This study aims to analyze the role of the community and local wisdom in facing the challenges of Islamic religious fanaticism and efforts to maintain Islamic culture in Masin Village. The research method used is a qualitative approach with a case study. Data were collected through in-depth interviews, observation, and documentation studies. The results showed that the people of Masin Village have a strong commitment to maintaining inter-religious harmony. Local wisdom such as the traditions of Earth Alms, Slametan, and Gotong Royong play an important role in minimizing Islamic religious fanaticism and maintaining a distinctive Islamic culture in the village. The conclusion of this research is that the active role of the community and the preservation of local wisdom are needed to maintain the balance between Islamic identity and religious harmony in Masin Village.